The Influence of The Use of SAP Applications (System Application and Product in Data Processing) on The Smoothness of Logistics At PT. Mitrabahtera Segara Sejati Samarinda - Suryadi, Awel; Widiatmaja, Arya; Putra, Renaldi Sanjaya (RSF Conference Series: Engineering and Technology, 2023)
Competition in the business world is increasing, and companies are trying to improve the quality of their companies by providing fast services and low costs compared to their competitors, one of which is in the logistics sector. To accelerate logistic activities, companies generally use application systems that are widely used today, called SAP (System Application and Product in Data Processing), which can integrate data. One of the companies that uses SAP is PT.Mitrabahtera Segara Sejati Samarinda. Therefore, the researchers analyzed the effect of using SAP on the smooth running of logistics at PT.Mitrabahtera Segara Sejati Samarinda. The method used in this research is the descriptive quantitative method, called simple linear regression analysis using SPSS, by distributing questionnaires with a total of 52 respondents who are employees of PT.Mitrabahtera Segara Sejati Samarinda. The result obtained from the test, called t-test with the result t-count > t-table (7.651 > 2.00), it can be said that the variable using the SAP application has a positive effect on logistics. The study results show a positive and significant influence related to the effect of using the SAP application on logistics at PT.Mitrabahtera Segara Sejati Samarinda.